DAMPAK PANDEMI COVID-19 TERHADAP KONTRIBUSI NILAI PERDAGANGAN INDONESIA-CHINA (CATRUWULAN I TAHUN 2020) - Emelia Lestari; Jumardi Budiman; Irfansius Roni Darmawan; Sigit Hardiyanto (Jurnal Pendidikan Ekonomi (JURKAMI), 2022)
The background of this research is the decline the value of exports from China to countries in Asia including Indonesia due to the Covid-19 pandemic since December 2019. Indonesia has imposed import restrictions on certain products from China to minimizing the spread of the Covid-19 virus. The purpose of this study is to analyze the value of Indonesia-China trade in the first quarter of 2020. The research method used was a descrptif quantitative with the main data being the value of exports and imports between Indonesia and China obtained from data from the Indonesian Central Statistics Agency. The results of the study of the data obtained, that trade between Indonesia and China still provides a fairly large contribution value to Indonesia's foreign trade. This contribution is expressed as a percentage of Indonesia's total exports to China and imports from China to Indonesia. The recommendation based on the results of this study is that Indonesia-China trade should be maintained because China is the main trading partner country to maintain the continuity of Indonesia's economy